Opacidade e transparência. Percurso por obras tridimensionais em Belo Horizonte: de adolescentes (1937) a espaço nº9 (1967) - Gisele Guedes Tomaz de Aquino Pessoa (2017)
The present research is dedicated to the construction of the history of art in Belo Horizonte through a compound path of the three-dimensional works present in the city. The itinerary consists of two phases: the first involves works considered modern and present in the city of Belo Horizonte, case of Adolescents (1937) sculpture of artist Jeanne Milde and part of the collection of the Mining Museum (MMI) and works located in Pampulha Architectural Complex built in 1943, are they the bas-relief produced by Alfredo Ceschiatti inside the Church of Saint Francis of Assisi; The Hug, also authored by Ceschiatti but in Pampulha Art Museum (MAP), Pampulha sculpture (or Winged Figure) of José Alves Pedrosa and the Nude by August Zamoinsky, who share the same location in the gardens of the MAP. The second moment consists in the selection of three-dimensional works awarded in the mucipal art salons of fine arts (SMBA) performed by the MAP in the editions of 1961 (XVI SMBA), 1963 (XVIII SMBA), 1965 (XX SMBA) and 1967 (XXII SMBA), of which will be analysed the sculptures The Sentinel of Francisco Stockinger, Untitled of Amílcar de Castro, The Bold of Nicolas Vlavianos and Space no. 9 of Hisao Ohara. The division adopted had in principle the construction of two blocks of analysis for understanding of respective stresses from threedimensional raised: the first to an idea of modern sculpture and the second in terms of specificity of tradicional sculptural practice.